Digital electronics : - Tokheim, Roger (McGraw-Hill Higher Education, 2008)
Digital Electronics: Principles and Applications, seventh editions, is an easy-to-read introductory text for students new to the field of electronics. Providing entry-level knowledge and skills for a wide range of occupations is the goal of this textbook and its ancillary materials. Prerequisites are general math and introductory electricity/electronics. Binary math, Boolean concepts, simple programming, and various codes are introduced and explained as needed...